Methodological Particularities in Research on Contemporary Childhood in Croatia: A Pedagogical – Psychological Perspective - Dubovicki, Snježana; Velki, Tena (Revija za elementarno izobraževanje, 2022)
The study aimed to determine the methodological particularities present in research on contemporary childhood. The study methodology involves an analysis of Croatian journals in which the subject of contemporary childhood has been published in the last two years. The inclusion criteria for article analysis were as follows: Social Science discipline, field of Pedagogy and Psychology, participants’ age (from 6 to 14 years) and the visibility of the journal citation. The analysis of the contemporary approach included methodological particularities. The results show that these studies of contemporary childhood do not apply “contemporary” approaches to the examination of childhood.
Keywords: contemporary childhood, pedagogy, psychology, qualitative methodology, quantitative methodology